Resident Case Series: Blood Flow Restriction as an Adjunct to Strengthening Exercises in Two Patients with Subacromial Impingement and High Irritability - Angel Ceballos; Giorgio Zeppieri Jr; Joel Bialosky (North American Sports Medicine Institute, 2022)
# Introduction Evidence informed management of individuals presenting with subacromial impingement syndrome (SAIS) includes strengthening exercises directed at the shoulder musculature. Patients with subacromial impingement syndrome (SAIS) can present with pain during and after completion of heavy resistance training limiting the applicability of this recommended treatment approach. Blood flow restriction (BFR) training is indicated for patients who have pain while completing heavy resistance training and may represent an important treatment modification for patients with SAIS unable to fully participate in a strengthening exercise program. The purpose of this case series is to describe the inclusion of BFR in the treatment of two patients with SAIS. # Case descriptions Two middle aged, non-operative patients with signs and symptoms consistent with SAIS and high levels of irritability were included. Treatment over one month consisted of three commonly used exercises in the treatment of SAIS in conjunction with a standard BFR protocol: 75 reps broken up into sets of 30,15,15,15 with the BFR cuff placed over proximal humerus. # Outcomes Immediate within session improvements beyond measurement error were observed in resting pain and pain pressure thresholds at three sites. At the end of the course of treatment, clinically meaningful improvements were observed in patient reported outcomes including the PENN Score, ASES score, and the patient-specific functional scale. Clinically meaningful improvements and change beyond measurement error were also observed in range of motion and strength which (assessed via a handheld dynamometer). # Discussion The incorporation of low load resistance training with BFR may be a useful adjunct for treating patients with SAIS to promote exercise-induced hypoalgesia, decrease pain, and increase function in the upper extremity. # Level of Evidence 5